Induced Pluripotent Stem Cells Derived from a CLN5 Patient Manifest Phenotypic Characteristics of Neuronal Ceroid Lipofuscinoses - Uusi-Rauva, Kristiina (Int J Mol Sci, 2017)
Neuronal ceroid lipofuscinoses (NCLs) are autosomal recessive progressive encephalopathies caused by mutations in at least 14 different genes. Despite extensive studies performed in different NCL animal models, the molecular mechanisms underlying neurodegeneration in NCLs remain poorly understood. To model NCL in human cells, we generated induced pluripotent stem cells (iPSCs) by reprogramming skin fibroblasts from a patient with CLN5 (ceroid lipofuscinosis, neuronal, 5) disease, the late infantile variant form of NCL. These CLN5 patient-derived iPSCs (CLN5Y392X iPSCs) harbouring the most common CLN5 mutation, c.1175_1176delAT (p.Tyr392X), were further differentiated into neural lineage cells, the most affected cell type in NCLs. The CLN5Y392X iPSC-derived neural lineage cells showed accumulation of autofluorescent storage material and subunit C of the mitochondrial ATP synthase, both representing the hallmarks of many forms of NCLs, including CLN5 disease. In addition, we detected abnormalities in the intracellular organelles and aberrations in neuronal sphingolipid transportation, verifying the previous findings obtained from Cln5-deficient mouse macrophages. Therefore, patient-derived iPSCs provide a suitable model to study the mechanisms of NCL diseases.